A comparative study of levobupivacaine 0.25% with dexmedetomidine and dexamethasone as adjuvant in caudal block for pediatric patients undergoing infraumbilical surgeries - Batula Shravani; Neelima Tandon; Man Mohan Jindal; Kushal Jethani (Asian Journal of Medical Sciences, 2024)
Background: The caudal epidural block is one of the most commonly used regional techniques for post-operative pain management in pediatric age group patients undergoing infraumbilical surgeries. Adjuvants use increase the duration of analgesia and decrease local anesthetic dose requirement, thereby decreasing the risk of toxicity. Aims and Objectives: The aim of the present study was to compare the prolongation of the duration of analgesia, hemodynamic parameters, and side effects if any, provided by the addition of dexmedetomidine (DEX) or dexamethasone as an adjuvant to levobupivacaine in the caudal block. Materials and Methods: A total of 60 patients with the American Society of Anesthesiologists grade I/II scheduled for elective infraumbilical surgeries were randomly allocated into two groups of 30 each. Group 1 received levobupivacaine 0.25% 1 mL/kg+DEX 1 mcg/kg and Group 2 received levobupivacaine 0.25% 1 mL/kg+dexamethasone 0.1 mg/kg for caudal block. The duration of analgesia, hemodynamic parameters, and adverse events during the post-operative period were noted. Results: There was no statistically significant difference in hemodynamic parameters between Group 1 and Group 2. Post-operative face, leg, activity, cry, consolability, (FLACC) pain scores were significantly lower in Group 1 when compared with Group 2. The mean duration of analgesia was prolonged in Group 1 at 824.23±53.53 min than in Group 2 with a mean duration of analgesia 480.50±31.66 min which was statistically significant (P<0.005). Adverse events were comparable between the two groups and were statistically not significant (P>0.05). Conclusion: The addition of DEX to levobupivacaine in caudal block significantly prolongs the duration of analgesia in post-operative period in comparison to the addition of dexamethasone with levobupivacaine. It also provides more hemodynamic stability during the intraoperative and post-operative period, lower FLACC pain scores, and is associated with minimal side effects.